1992
DOI: 10.1210/endo.131.2.1639013
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulation of messenger ribonucleic acid for the surfactant-associated proteins in human fetal lung in vitro.

Abstract: Respiratory distress syndrome (RDS) is primarily caused by an immaturity in the synthesis and secretion of surfactant by the fetal lung type II cell. Fetal hyperinsulinemia associated with maternal diabetes places the newborn at an increased risk of developing RDS, and therefore, it has been hypothesized that insulin inhibits type II cell differentiation. We have previously shown that insulin inhibits the accumulation of surfactant-associated protein A (SP-A), the major surfactant-associated protein, in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
0
16
1
1
Order By: Relevance
“…As fetal hyperinsulinemia associated with maternal diabetes is associated with a reduction in SP-A protein in amniotic fluid (42) and an increased risk of developing RDS in the newborn, it has been hypothesized that insulin inhibits type II cell differentiation. Subsequently, it was shown that insulin administration to human fetal lung tissue explants inhibits both SP-A and SP-B gene expression (8). As the IUGR fetus is characterized by hypoglycemia and concomitant hypoinsulinemia (40), this pathway is unlikely to be the mechanism for the observed inhibition of SP mRNA or protein expression in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…As fetal hyperinsulinemia associated with maternal diabetes is associated with a reduction in SP-A protein in amniotic fluid (42) and an increased risk of developing RDS in the newborn, it has been hypothesized that insulin inhibits type II cell differentiation. Subsequently, it was shown that insulin administration to human fetal lung tissue explants inhibits both SP-A and SP-B gene expression (8). As the IUGR fetus is characterized by hypoglycemia and concomitant hypoinsulinemia (40), this pathway is unlikely to be the mechanism for the observed inhibition of SP mRNA or protein expression in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…The frozen tissues (50-100 mg) were homogenized in 1 ml of RNA extraction mixture, and total RNA was isolated as described previously (22,23). The precipitated total RNA pellet was washed with 1 ml 75% ethanol, air-dried, and resuspended in 25 ml sterile diethylpropylcarbonate-treated water (24).…”
Section: Rna Isolationmentioning
confidence: 99%
“…The precipitated total RNA pellet was washed with 1 ml 75% ethanol, air-dried, and resuspended in 25 ml sterile diethylpropylcarbonate-treated water (24). Following quantitation of total RNA by determining the ultraviolet (UV) absorbence at 260 nm, equal amounts of total RNA (10 g) from each sample were separated by gel electrophoresis on a 1.0% agarose/5% formaldehyde gel, and was capillary transferred to Nytran Plus membranes (Schleicher & Schuell, Keene, NH) using a phosphate buffer as described previously (23). The ethidium bromide-stained ribosomal RNA bands in the agarose gel were photographed on a UV lightbox.…”
Section: Rna Isolationmentioning
confidence: 99%
“…Fetal lung explants (prepared from distal lung tissue) that had been maintained in vitro for 6 days and an adult lung adenocarcinoma cell line (NCI-H441 cells) were used as positive controls for some experiments [15,16]. Both the cultured fetal lung explants and the H44l cells produce both human SP-A proteins (SP-Al and SP-A2) and SP-B [11,17]. The fetal lung explants also produce SP-C [17].…”
Section: Tissuementioning
confidence: 99%
“…Both the cultured fetal lung explants and the H44l cells produce both human SP-A proteins (SP-Al and SP-A2) and SP-B [11,17]. The fetal lung explants also produce SP-C [17].…”
Section: Tissuementioning
confidence: 99%